Anticipatory responsible innovation: Futures construction in the face of the techno-economic imperative - Rodríguez, Hannot; Urueña, Sergio; Ibarra, Andoni (NOvation — Critical Studies of Innovation, 2022)
The call for the development of more responsible research and innovation has increasingly permeated European Union research and development policies. Specifically, under the auspices of approaches such as “Responsible Research and Innovation” (RRI) and “Open Science”, these policies conceive of the need to make innovation dynamics radically open and debatable, even with regard to the underlying preferences and expectations shaping them. Responsibility has thus been conceived in eminently anticipatory terms, that is, in terms of collectively taking care in the present of the futures enabled through innovation practices. This normative conception, which emphasises the politicisation of the ways futures are constructed through innovation and goals they are oriented towards, is nonetheless realised within a context where the prevailing way of approaching the future with regard to innovation systems is highly committed to a capitalist imperative of technological progress and economic growth. This article argues that while anticipation – understood as an interventive practice – can deploy valuable responsibilisation heuristics, their degree of disruptiveness, or openness, may depend on how such interventive practice engaging with futures deals with this techno-economic commitment, or imperative.